SAJAK-SAJAK BADARUDDIN H.O. BERTEMAKAN KETUHANAN: ANALISIS PENDEKATAN DAKWAH - Pg. Ahmad, Pg. Haji Yakup; Abu Hassan, Mohamad Mokhtar (Jurnal Pengajian Melayu (JOMAS), 2018)
This paper analyses the poems of Badaruddin H.O., a famous poet of Brunei whose work is Islamic-themed with particular reference to God. The works examined include “Although Your Home In The Hereafter” (Meski Rumah Mu Di Akhirat), “Istighfar Rejab” (Istighfar Rejab), “This Is Not My Baby” (Ini Zat Bukan Bayangku), “Tsunami’s Episodes” (Episod-Episod Tsunami), “It’s Fate” (Takdir Itu Begini), “In The Holy Night of Ramadan” (Di Malam Kudus Ramadan), and “White Stick” (Tongkat Putih). His poems are then analysed through a da’wah (missionizing) theoretical approach, which identifies da’wah elements that display the majesty of God, and the gentle language style that conveys the religious message. Keywords: Malay methodology, da’wah, prophecy, rukun Islam, rukun Iman.